Persepsi Mahasiswa Atas Kegunaan Dan Kemudahan Teknologi Terhadap Adopsi Teknologi Kecerdasan Buatan di Bidang Akuntansi - Julian, Julian Stevanus Salim; Trifena Agustina; Saskia Jamilah Khairany (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This study aims to analyze the influence of perceived usefulness and ease of use on the adoption of Artificial Intelligence (AI) technology in accounting among accounting students in Palembang. The research addresses the issue of low readiness and limited understanding of AI technology among students, despite its growing importance in modern accounting practices. A quantitative approach was applied using the Technology Acceptance Model (TAM), with regression analysis conducted through SmartPLS based on responses from 244 participants. The results indicate that perceived usefulness has a positive and significant effect on AI adoption (coefficient = 0.371; p = 0.000), as does perceived ease of use (coefficient = 0.286; p = 0.004). These findings suggest that the more useful and user-friendly the technology is perceived to be, the more likely students are to adopt AI. Thus, educational institutions should enhance students’ technological understanding and skills through AI-integrated curricula and training programs.